CONFIDENCE: BEFORE AND AFTER ORAL RECITATIONS - Jerald Cano-og Moneva; Audrey Jane Paclipan Cuizon (Journal of Applied Linguistics and Literature, 2020)
A belief in one’s capability to do and perform the task well is referred to as self-confidence. Meanwhile, oral recitation is a form of speaking in front of other people to report information. Hence, this study was conducted in Jagobiao National High School- Senior High School Department. The researcher-made likert scale questionnaire was used to assess the students from the different strands, aimed to know the students’ confidence regarding their oral recitation performance and students’ confidence before and after they perform oral recitations. Moreover, the quantitative data were analyzed through weighted mean and paired samples t-test. In which, the result shows improvement of students’ confidence after ten or more times of performing oral recitations due to their intensive oral participation. It means that when a student is highly confident then she or he is able to perform the oral participation efficiently. Thus, it revealed that there is a significant difference between students’ confidence before and after oral recitations. In this study, suggestions were provided to students such as engaging in different activities that could enhance their confidence in all aspect and to the teachers and parents who need to help the students to perform well in school with self-confidence.